Reductive Dechlorination of the Nitrogen Heterocyclic Herbicide Picloram - Ramanand, K. (1993)
The anaerobic biodegradation of picloram (3,5,6-trichloro-4-amino-2-pyridinecarboxylic acid) in freshwater sediment was favored under methanogenic conditions but not when sulfate or nitrate was available as a terminal electron acceptor. Under the former conditions, more than 85% of the parent substrate (340 μM) was removed from nonsterile incubations in 30 days, following a 50-day acclimation period. Concomitant with substrate decay, an intermediate transiently accumulated in the sediment slurries. By liquid chromatography-mass spectrometry, the intermediate was identified as an isomer of dichloro-4-amino-2-pyridinecarboxylic acid. Proton nuclear magnetic resonance evidence suggested that a chlorine was reductively removed from the parent substrate at the position meta to the nitrogen heteroatom. Upon continued incubation, the dechlorinated product was transformed into an unidentified compound which accumulated and resisted further decay. The addition of sulfate or bromoethanesulfonic acid to sediment slurries inhibited picloram dehalogenation, but molybdate reversed the inhibitory effect of sulfate on pesticide metabolism. These findings help clarify the fate of a halogenated nitrogen heterocyclic herbicide in anaerobic environments.